2002
DOI: 10.4049/jimmunol.168.3.1050
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Mucosal Addressin Cell Adhesion Molecule-1+ High Endothelial Venule Cells (HEV) and Identification of a Leucine-Rich HEV Glycoprotein as a HEV Marker

Abstract: High endothelial venule (HEV) cells support lymphocyte migration from the peripheral blood into secondary lymphoid tissues. Using gene expression profiling of mucosal addressin cell adhesion molecule-1+ mesenteric lymph node HEV cells by quantitative 3′-cDNA collection, we have identified a leucine-rich protein, named leucine-rich HEV glycoprotein (LRHG) that is selectively expressed in these cells. Northern blot analysis revealed that LRHG mRNA is ∼1.3 kb and is expressed in lymph nodes, liver, and heart. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 46 publications
0
61
0
Order By: Relevance
“…TGF-β was reported to increase granulocyte/macrophage-colony stimulating factor (GM-CSF)-driven granulocyte differentiation, which was postulated to occur via increased surface expression of the GM-CSF receptor induced by TGF-β [29]. Recently, Saito et al reported isolation of LRG from high endothelial venule cells and proposed a role for LRG in adhesive interactions between lymphocytes and the endothelium [30]. They also reported that LRG immobilized on plastic wells could bind to TGF-β in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β was reported to increase granulocyte/macrophage-colony stimulating factor (GM-CSF)-driven granulocyte differentiation, which was postulated to occur via increased surface expression of the GM-CSF receptor induced by TGF-β [29]. Recently, Saito et al reported isolation of LRG from high endothelial venule cells and proposed a role for LRG in adhesive interactions between lymphocytes and the endothelium [30]. They also reported that LRG immobilized on plastic wells could bind to TGF-β in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Tissue-specific and vessel type-specific differences in ECs have also been detected at the transcriptional level by subtractive hybridization technologies 11,12 or gene expression profiling. [13][14][15] For instance, several tumor-specific EC molecules were identified by comparing gene expression patterns of ECs freshly isolated from blood vessels of normal or malignant colorectal tissue. 14 Although the molecular diversity of ECs is now clearly established, the origin of this heterogeneity remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…While looking for genes specifically expressed in HEVs (11,12) we noticed that transcripts for a B cell chemokine CXCL13/ BLC were found in low abundance in cDNA libraries that we generated from PNAd ϩ HEVs and MAdCAM-1 ϩ HEVs. Therefore, we performed immunohistochemical analyses to examine whether CXCL13 is expressed in HEVs at the protein level.…”
Section: Cxcl13 Is Expressed In the Majority Of Hevsmentioning
confidence: 99%
“…Biotinylated anti-mouse CCL19, anti-mouse CCL21 and anti-mouse CXCL12 Abs were obtained from DAKO (Glostrup, Denmark), PeproTech (Rocky Hill, NJ) and Santa Cruz Biotechnology, respectively. MECA-79 (anti-peripheral node addressin (PNAd)) and MECA-367 (anti-mucosal addressin cell adhesion molecule (MAdCAM)-1) were kindly provided by Dr. E. C. Butcher (Stanford University, Stanford, CA) and used as described (11,12). Biotin-conjugated mAbs to CD3, B220, and CD11b were from BD PharMingen (San Diego, CA).…”
Section: Antibodiesmentioning
confidence: 99%